Gli intellettuali e la riforma della scuola: un dibattito sulle pagine di «Rinascita» - Pietro Maltese (Firenze University Press, 2010)
The author analyzes, from the Second World War, the debate around school reform born on the pages of «Rinascita». The protagonists were scholars of the caliber of Marchesi L. Lombardo Radice, Banfi and enlargement of the main issues focused around education for the working classes as a means of social ascent (and here he became interested Lombardo Radice). They discussed also the opportunity to bring the school post primary the model of classical humanistic culture or adapt to technical requirements of the manufacturing world. On the pages of «Rinascita» these issues were discussed for many years with great interest.